Liability of Land Deed Official (The PPAT) on Falsifying Document Under Indonesian Land Regulations - Muhammad Ilham Sumartoputra; Firman Turmantara Endipradja (International Journal of Latin Notary, 2020)
Head of Sub-District as Temporary Land Registrar can be said to have the same authority as PPAT as official land deed maker, however in practice the Sub-District Head as Temporary PPAT often ignores existing regulations regarding deed, such as not reading the deed so that the contents of the land sale certificate cannot be understood by party. In addition, in the contents of the document there are many "entries" that are left blank so that doubts about the legal power of the deed he made becomes real. Based on the foregoing, the identification of the problem carried out is how the camat's responsibility as the official maker of temporary land deeds to the parties harmed by the deed he made is related to Government Regulation No. 37 of 1998 concerning Land Deed Officials, how to protect the parties in making authentic deeds by the sub-district head as the official maker of temporary land deeds are associated with Government Regulation No. 37 of 1998 concerning Officials of Land Deed and How to Settle due to the Sub-District's negligence in making authentic deeds by camat as temporary land deed official. The specification of the research carried out is descriptive analytical, namely research by describing systematically, accurately, actually and comprehensively regarding the Acting Land Acting Officer. Method The approach used is normative juridical, namely research on legal principles carried out with legal norms which is a benchmark for behaving. The research phase used is through library research and field research. The conclusion in this thesis is the responsibility of the subdistrict head as the official of the deed of land against the parties who were harmed by the deed he made related to Government Regulation No. 37 of 1998 concerning the Acting Officer of Land Deed, while holding the responsibility accountable for negligence resulting in another person suffered losses, a form of accountability by receiving civil sanctions. The form of this civil sanction is with reimbursement of costs, interest and compensation, so that if an act is detrimental to the parties in making a deed, then the camat is responsible for all losses suffered by the parties. In addition, the legal protection of the parties in making authentic deeds by the camat as the official maker of temporary land deeds associated with Government Regulation No. 37 of 1998 concerning Land Deed Makers is the Camat as the head of the region has the duty and authority to advance his territory and is authorized in making authentic deeds, this is due to the legalization of the sub-district head as the official maker of temporary land deeds. Therefore, the parties are obliged to obtain legal protection from legal products issued by the Camat as temporary land deed-making officials.